Woman Stereotype in the Novel Convenience Store Woman by Sayaka Murata (2016) - Mutiara Oktavia Herlina; Muhd. Al Hafizh (Universitas Negeri Padang, 2022)
This article discusses a novel entitled Convenience Store Woman (2016) by Sayaka Murata. The issue raised is about the stereotype of women who are influenced by patriarchal culture and gender discrimination in society. This article aims to explain the forms of woman stereotypes and also show how woman characters can breaks these stereotypes. The descriptive qualitative method was used in this research, which applied Simone De Beauvoir's theory of existentialist feminism and Mansour Fakih's concept of gender discrimination about the relationship with the concept of gender that leads to discrimination. The results of the analysis show that the stereotype of women consists of three forms, namely women as mothers, women as incompetent people, women as sex objects.